Pengkajian dan Manajemen Nyeri Pasien Sakit Kritis di Intensive Care Unit - Dimas Kusnugroho Bonardo Pardede; Fadhil Mochtar (Jurnal Medika Hutama, 2024)
Abstract Pain is commonly found in critically ill patients admitted to intensive care unit (ICU). Inability of verbal communication due to disease, muscle relaxant, restraint or sedation and critical condition due to organ dysfunction are barriers in pain assessment and management which might increase the risk of underrated and undertreated pain thus increasing morbidity and mortality. Pain management in critically ill patients includes pain assessment using reliable instruments accompanied with adequate, evidence-based and multi-modal strategies incorporating both non-pharmacologic and pharmacologic treatment. Keywords : critical illness; ICU; pain